2020
DOI: 10.1093/cercor/bhz341
|View full text |Cite
|
Sign up to set email alerts
|

Topologically Guided Prioritization of Candidate Gene Transcripts Coexpressed with the 5-HT1A Receptor by Combining In Vivo PET and Allen Human Brain Atlas Data

Abstract: The serotonin-1A receptor (5-HT1AR) represents a viable target in the treatment of disorders of the brain. However, development of psychiatric drugs continues to be hindered by the relative inaccessibility of brain tissue. Although the efficacy of drugs selective for the 5-HT1AR has not been proven, research continues to focus on drugs that influence this receptor subtype. To further knowledge on this topic, we investigated the topological coexpression patterns of the 5-HT1AR. We calculated Spearman’s rho for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…By including whole-brain gene expression patterns, our approach can be discriminated from previous imaging genetics studies investigating effects of individual disease-related single-nucleotide polymorphisms or environmental factors. This study adds up to numerous wide-ranging research findings combining topological mRNA expression with fMRI measures (Richiardi et al, 2015; Shin et al, 2018) or other neuroimaging properties, partially offering toolboxes for an integrative data analysis (Rizzo et al, 2016; Unterholzner et al, 2020). Furthermore, the hierarchically structured GO database was successfully applied in an attempt to find a relationship between well-defined biological processes and imaging properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By including whole-brain gene expression patterns, our approach can be discriminated from previous imaging genetics studies investigating effects of individual disease-related single-nucleotide polymorphisms or environmental factors. This study adds up to numerous wide-ranging research findings combining topological mRNA expression with fMRI measures (Richiardi et al, 2015; Shin et al, 2018) or other neuroimaging properties, partially offering toolboxes for an integrative data analysis (Rizzo et al, 2016; Unterholzner et al, 2020). Furthermore, the hierarchically structured GO database was successfully applied in an attempt to find a relationship between well-defined biological processes and imaging properties.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, post-mortem gene expression data from the Allen Human Brain Atlas (AHBA) was repeatedly applied to investigate the relationship between the transcriptome and protein distribution 3 , brain connectivity 4 , or morphology 5 . These studies add up to numerous wideranging research findings combining topological mRNA expression with neuroimaging properties, partially offering toolboxes for an integrative data analysis 6,7 . Different methods offer designated benefits and disadvantages, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a disease that is primarily associated with loss of dopaminergic neurons, one would expect strongest imaging changes in regions, which contain many of such neurons in healthy individuals. While promising, this approach also makes several assumptions that do not necessarily hold or are unknown for many of the underlying systems (Unterholzner et al, 2020). For example, correlations with mRNA expression imply that the respective genes are transcribed and lead to measurable changes of tissue structure or function.…”
Section: Introductionmentioning
confidence: 99%
“…Using the Allen Human Brain Atlas (AHBA; http://human.brainmap.org ) ( Hawrylycz et al, 2012 ), numerous studies investigating the relationship between structural and functional brain parameters and the transcriptome were published recently ( Burt, 2018 ; Goel et al, 2014 ; Richiardi et al, 2015 ; Shin et al, 2017 ). Several authors showed close associations of gene expression levels with in vivo protein densities, mainly focusing on serotonergic neurotransmitter receptors ( Komorowski et al, 2017 ; Rizzo et al, 2016 ; Unterholzner et al, 2020 ). Similar to the serotonergic system, dopamine signaling is mediated through G-protein-coupled receptors and plays a crucial role in physiologic and pathologic processes in humans, including neuropsychiatric conditions ( Beaulieu and Gainetdinov, 2011 ).…”
Section: Introductionmentioning
confidence: 99%